Review paperNailfold capillaroscopy. Microscopic assessment of microcirculation abnormalities in systemic sclerosis - Michalska-Jakubus, Małgorzata; Chodorowska, Grażyna; Krasowska, Dorota (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2010)
Nailfold capillaroscopy is a non-invasive diagnostic method that allows the in vivo assessment of skin microcirculation. It is most widely used in the field of rheumatology and dermatology, especially for differentiating primary and secondary Raynaud’s phenomenon as well as for diagnosing and monitoring patients with systemic sclerosis. The most characteristic structural changes in microcirculation are present in systemic sclerosis – they appear in the early stage of disease and play an essential role in pathogenesis. The present study presents the basics of capillaroscopic examination, its use in clinical practice and its role in the diagnosis of patients with Raynaud’s phenomenon and systemic sclerosis.